Konsep Belajar dan Pembelajaran - Tiara Dwi Putri; Zumirrahilza Haq; Gusmaneli Gusmaneli (Lembag, 2025)
The concepts of learning and instruction are central to the educational process and continue to evolve in response to changes in society and technology. In the modern context, the shift from teacher-centered to student-centered paradigms demands a more comprehensive understanding of both concepts. This study aims to analyze the essence of learning and instruction from various theoretical perspectives and evaluate their relevance to current educational practices. The research employs a library research method, examining relevant scholarly literature including books, journals, and academic documents. The findings indicate that a proper understanding of learning and instruction significantly influences the teaching strategies applied by educators and contributes to the development of independent and adaptive learners. This study is expected to serve as a foundation for designing more contextual and responsive instructional approaches in today’s educational landscape.